F-box protein 43 promoter methylation as a novel biomarker for hepatitis B virus-associated hepatocellular carcinoma - Zhang, Ying; Wang, Jing-Wei; Su, Xing; Li, Jin-E; Wei, Xue-Fei; Yang, Jie-Ru; Gao, Shuai; Fan, Yu-Chen; Wang, Kai (Frontiers in Microbiology, 2023)
Background: Hepatocellular carcinoma has a high prevalence and poor prognosis worldwide. Therefore, it is urgent to find effective and timely diagnostic markers. The objective of this study was to evaluate the diagnostic value of F-box protein 43 promoter methylation in peripheral blood mononuclear cells (PBMCs) for hepatocellular carcinoma (HCC). Method: A total of 247 participants were included in this study, comprising individuals with 123 hepatitis B virus-associated HCC, 79 chronic hepatitis B and 45 healthy controls. F-box protein 43 methylation and mRNA levels in peripheral blood mononuclear cells were detected by Methylight and quantitative real-time PCR. Result: F-box protein 43 promoter methylation levels were significantly lower in hepatocellular carcinoma PBMCs than in the chronic hepatitis B (P < 0.001) and healthy controls PBMCs (P < 0.001). Relative mRNA expression levels of F-box protein 43 in hepatocellular carcinoma PBMCs were significantly higher than that in chronic hepatitis B (P < 0.001) and healthy controls PBMCs (P < 0.001). Receiver operating characteristic analysis of F-box protein 43 promoter methylation levels yielded an Area Under Curve (AUC) of 0.793 with 76.42% sensitivity and 68.35% specificity, when differentiating hepatocellular carcinoma from chronic hepatitis. These value for F-box protein 43 promoter methylation level was superior to that of alpha-fetoprotein serum (AFP) level (AUC: 0.780, sensitivity: 47.97%, and specificity: 96.20%), with increments in values for the combination of F-box protein 43 promoter methylation AFP levels (AUC: 0.888, sensitivity: 76.42%, and specificity: 86.08%). Conclusion: Hypomethylation of the F-box protein 43 promoter in PBMCs is a promising biochemical marker for HBV-associated hepatocellular carcinoma.